MORALIS (Paradigma Baru dalam Etika Bisnis Modern) - Rudi Haryanto (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2009)
Human life naturally needs a perfect moral norm system tobridge social clash caused by the different right andinterest. In this condition, the uniformity of values isrequired by human to create a well-ordered life. It isreligion, as the highest authority of truth that could launcha uniformity of values. Islam, as the total way of life, haspurposed a sequence of business concepts containing auniversal moral-ethic principle. According to Islamicconcept, business and moral cannot be separated to eachother. An Islamic business moral ethic values reflectsunity, equilibrium, free will, responsibility, truth, gooddeeds and honesty. This article discloses how a businessmust be run on the basis of Islamic business moral ethicvalues. Some people assume the practice of Islamicbusiness generates a gap between ideality and reality.However, an intensive study on these concepts has beendone to establish Islamic moral ethic values becomingbusiness reference. Consequently, an ethic-expectation ofsociety demands business activists that are moralists. Thisis to uphold ethic in business as well as to survive inrunning it.